KOMPETENSI SUMBERDAYA MANUSIA, SISTEM PENGENDALIAN INTERNAL DAN PENGARUHNYA TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN - Zahro, Nafi’ Inayati (Proceeding SENDI_U, 2015)
This research take theme about human resource competence,internal control system and its Influence to the qualityFinancial Statement information. The purpose of this research are to examine the influence of human resourcecompetence toward the quality of financial statement information, and to examine internal control system influencetoward the quality of financial statement information. Population from this research is all of local governmentofficer in Central Java. Sample in this research is taken by purposive sampling, the sample taken at SKPD all-EksKaresidenan Pati. Examination hypothesis conducted by using Multiple Regression Analysis. The Dependentvariable for the research is the financial statement information quality, while independent variable is humanresource competence and internal control system. The Result of this research show that human resource competenceand internal control system have significant influence which the quality of financial statement information.Key words: resource, control. Accounting, government, stateme